Associations between health behaviors and mental health in Australian nursing students. (May 2021) - Stanton, Robert; Best, Talitha; Williams, Susan; Vandelanotte, Corneel; Irwin, Christopher; Heidke, Penny; Saito, Amornrat; Rebar, Amanda L.; Dwyer, Trudy; Khalesi, Saman
Abstract: Aim: Nursing students experience high levels of stress, anxiety and depression. This study examined associations between health behaviors and stress, anxiety and depression in Australian nursing students. Design: this was a cross-sectional study. Methods: Participants completed an online survey providing demographic information and responses to the 21-item Depression Anxiety Stress Scale, Fagerström Test for Nicotine Dependence, short Food Frequency Questionnaire, Alcohol Use Disorders Identification Test, International Physical Activity Questionnaire and Workforce Sitting Questionnaire. Associations were evaluated using multivariate linear regression. Results: Mild to extremely severe stress (46.6%), anxiety (52.8%) and depression (42.2%) were prevalent. Intake of snack-foods was associated with higher depression (β = 8.66, p  < 0.05) and stress (β = 3.92, p  = 0.055) scores. More time spent sitting was associated with higher depression (β = 0.48, p  < 0.001) and stress (β = 0.28, p  < 0.05) scores. Skipping meals correlated with higher stress, anxiety and depression scores. Conclusion: More support must be provided to nursing students to manage psychological distress and mental health during university study. Highlights: Almost half of nursing students surveyed report elevated psychological distress. Metropolitan students report higher psychological distress than regional students. Sociodemographic characteristics are associated with psychological distress. Poor health behaviors increased the likelihood of elevated psychological distress. Curricula-based support may reduce risk factors for psychological distress.